2012
DOI: 10.1016/j.ultramic.2012.07.021
|View full text |Cite
|
Sign up to set email alerts
|

Highly reproducible low temperature scanning tunneling microscopy and spectroscopy with in situ prepared tips

Abstract: An in situ tip preparation procedure compatible with ultra-low temperature and high magnetic field scanning tunneling microscopes is presented. This procedure does not require additional preparation techniques such as thermal annealing or ion milling. It relies on the local electric-field-induced deposition of material from the tip onto the studied surface. Subsequently, repeated indentations are performed onto the sputtered cluster to mechanically anneal the tip apex and thus to ensure the stability of the ti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…The lower number of repeating conductance traces may be attributed to the fact that our tip is not purely Au, but PtIr covered with Au. In the experiments of Andres et al [29] with a graphene surface covered with a small cluster of Au, the number of repeating traces was also limited, in their case to 16. It has been reported that this repetition behavior during mechanical annealing is different for different materials [30] .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The lower number of repeating conductance traces may be attributed to the fact that our tip is not purely Au, but PtIr covered with Au. In the experiments of Andres et al [29] with a graphene surface covered with a small cluster of Au, the number of repeating traces was also limited, in their case to 16. It has been reported that this repetition behavior during mechanical annealing is different for different materials [30] .…”
Section: Methodsmentioning
confidence: 99%
“…This work on mechanical annealing was inspired by earlier break junction and STM experiments, supported by molecular dynamics simulations [25,2728]. A first application of this approach for a Au STM tip over a graphene surface [29] was made by first locally depositing Au on the graphene surface from the tip using a high electric field pulse, followed by mechanical annealing similar to [25] over that Au deposit. The authors confirmed that the method improved the topographic contrast of the surface and the quality of the spectroscopic data.…”
Section: Introductionmentioning
confidence: 99%
“…For atomically resolved STM experiments, tungsten tips are cleaned and sharpened in situ in UHV using hightemperature annealing [58], electric field restructuring [59][60][61][62][63][64][65], coaxial ion milling [66][67][68][69], and controllable tip crash using voltage pulses or contact between tip and sample [70,71]. Sometimes scanning at high tunneling currents and high bias voltages are applied to sharpen STM tips in tunneling regime.…”
Section: Preparation Of Tips and Samples For High-resolution Stm Expementioning
confidence: 99%
“…14 We have, therefore, employed a recently developed technique to prepare highly stable STM tips in situ at cryogenic temperatures. 15 Briefly, this method relies on local electric-field-induced deposition of material from the tip onto the studied surface. Subsequently, repeated indentations are gently performed onto the sputtered cluster to mechanically anneal the tip apex and thus to ensure the stability of the tip.…”
mentioning
confidence: 99%
“…Subsequently, repeated indentations are gently performed onto the sputtered cluster to mechanically anneal the tip apex and thus to ensure the stability of the tip. 15 After the sample is transferred to the 3 He cryostat, its quality is checked by measuring its STM topography in the constant current STM mode. The presence of monolayer graphene can be easily recognized in the STM images by a characteristic triangular array of bumps with an average separation of around 3 nm.…”
mentioning
confidence: 99%